Dark matter search with long-lived particles with the CMS experiment at the LHC - Orzari, Breno [UNESP] (Universidade Estadual Paulista (Unesp), 2025)
In this work, two projects are presented: improvements to the CMS pixel tracking algorithm and a search for dark matter particles at the CMS detector. The improvements to the HLT pixel tracks reconstruction algorithm were performed to address two issues: the hard maintainability, given that the reconstruction code is duplicated, and the exclusivity to a given accelerator device in the process of reconstructing events. The usage of a performance portability library allows for the solution of these issues, by having only one piece of the code that is compiled for distinct devices. Besides solving both issues, these improvements will play a fundamental role during the HL-LHC era. The search for dark matter particles is performed in terms of the AMSB model, which contains a charged unstable particle, the chargino, that decays inside the CMS detector into products that are not reconstructed. This process signature in the detector is that of a charged particle track that vanishes in the internal layers. One of the decay products is the neutralino, which is the lightest supersymmetric particle and is a dark matter candidate. The search for disappearing tracks was done using 62.5 fb^-1 data collected by the CMS experiment with a center-of-mass energy of sqrt{s} = 13.6 TeV during 2022 and 2023. Given that the CMS collaboration still blinds this data analysis, the results are interpreted in terms of expected exclusion regions with 95% CLs using data from the control regions of the search. Considering the Run 3 data only, a wino-like chargino is expected to be excluded up to a mass of 777 (405) GeV for a lifetime of 3 (0.2) ns, while a higgsino-like chargino is expected to be excluded up to a mass of 650 (354) GeV for a lifetime of 3 (0.2) ns. When combining this result to the previous Run 2 results, a wino-like chargino is expected to be excluded up to a mass of 904 (511) GeV for a lifetime of 3 (0.2) ns, while a higgsino-like chargino is expected to be excluded up to a mass of 762 (437) GeV for a lifetime of 3 (0.2) ns.

Neste trabalho, dois projetos são apresentados: melhorias no algoritmo de reconstrução de traços utilizando o detector de pixels do CMS e uma busca por partículas de matéria escura no detector do CMS. As melhorias no algoritmo de reconstrução de traços de pixels do HLT foram realizadas para abordar dois problemas: a difícil mantenabilidade, dado que o código da reconstrução é duplicado, e a exclusividade para um determinado dispositivo acelerador no processamento da reconstrução de eventos. O uso de uma biblioteca de portabilidade de performance permite a solução desses problemas, tendo apenas uma cópia do código compilada para dispositivos distintos. Além de resolver ambos os problemas, essas melhorias desempenharão um papel fundamental durante a era HL-LHC. A busca por partículas de matéria escura é realizada em termos do modelo AMSB, que contém uma partícula instável carregada, o chargino, que decai no interior do detector do CMS em produtos que não são reconstruídos. A assinatura desse processo no detector é a de um traço de partícula carregada que desaparece nas camadas mais internas. Um dos produtos do decaimento é o neutralino, que é a partícula supersimétrica mais leve e é um candidato à matéria escura. A busca por traços evanescentes foi feita utilizando 62,5 fb^-1 de dados coletados pelo experimento do CMS com uma energia de centro de massa de sqrt{s} = 13.6 TeV durante 2022 e 2023. Dado que esta análise de dados ainda está cega pela colaboração do CMS, os resultados são interpretados em termos de regiões de exclusão esperadas com CLs de 95% usando dados das regiões de controle da busca. Considerando apenas os dados do Run 3, espera-se a exclusão de um chargino do tipo wino até uma massa de 777 (405) GeV, para um tempo de vida de 3 (0.2) ns, e de um chargino do tipo higgsino até uma massa de 650 (354) GeV, para um tempo de vida de 3 (0.2) ns. Ao combinar este resultado com os resultados do Run 2 anterior, espera-se a exclusão de um chargino do tipo wino até uma massa de 904 (511) GeV, para um tempo de vida de 3 (0.2) ns, e de um chargino do tipo higgsino até uma massa de 762 (437) GeV, para um tempo de vida de 3 (0.2) ns.
Busca por matéria escura com partículas de vida longa no experimento CMS do LHC
Keywords: Aceleradores de Partículas; Física além do Modelo Padrão; Matéria escura - Astronomia; Dark matter (Astronomy); Particles (Nuclear Physics); Particle Accelerators; Partículas (Física nuclear)